Analyzer-based imaging system performance in a synchrotron clinical environment: a feasibility study. (17th February 2017) - Arfelli, F.; Menk, R.H.; Khromova, A.; Dreossi, D.; Pinamonti, M.; Zanconati, F.; Rigon, L.
Abstract: X-ray phase contrast imaging arises from changes of the propagation direction of the radiant wave field when traversing the object and it can yield higher contrast for soft tissues than conventional x-ray radiology based on attenuation. Commonly intermediate steps are required to transform wave front modulations into intensity modulations measurable by the detection system. One of these phase contrast techniques is analyzer-based imaging (ABI), which utilizes an analyzer crystal as angular filter with a bandwidth in the micro-radian regime placed between the sample and the detector. Furthermore employing appropriate algorithms, attenuation, refraction and scattering/dark field images can be extracted providing complementary information. The implementation of ABI requires X-ray optics with very high stability and micro-radian resolution. In return, this method possesses an extremely high sensitivity among the phase contrast techniques. At the medical beamline of the Italian synchrotron ELETTRA, a patient room has been implemented in order to perform clinical mammography with free-space propagation phase contrast. In this work we have tested the feasibility of ABI in a preclinical set-up implementing the system in the patient room. High quality images of breast tissues samples are presented and compared to images acquired at a conventional mammography unit. The system has shown excellent stability and imaging performances.